Au@109Pd core-shell nanoparticle conjugated to trastuzumab for the therapy of HER2+ cancers: studies on the applicability of 109Pd/109mAg in vivo generator in combined β− auger electron therapy - Nasrin Abbasi Gharibkandi; Kamil Wawrowicz; Agnieszka Majkowska-Pilip; Kinga Żelechowska-Matysiak; Mateusz Wierzbicki; Aleksander Bilewicz (SpringerOpen, 2023)
Abstract Background In radionuclide therapy, to enhance therapeutic efficacy, an intriguing alternative is to ensure the simultaneous implementation of low- and high-LET radiation emitted from a one radionuclide. In the present study, we introduce the concept of utilizing 109Pd (T1/2 = 13.7 h) in the form of a 109Pd/109mAg in vivo generator. In this system, 109Pd emits beta particles of medium energy, while 109mAg releases a cascade of conversion and Auger electrons. 109Pd was utilized in the form of 15 nm gold nanoparticles, which were coated with a monolayer of 109Pd. In this system, the 109Pd atoms are on the surface of the nanoparticle, while the 109mAg atoms generated in the decay reaction possess the capability for unhindered emission of Auger electrons. Results 109Pd, obtained through neutron irradiation of natural palladium, was deposited onto 15-nm gold nanoparticles, exceeding a efficiency rate of 95%. In contrast to previously published data on in vivo generators based on chelators, where the daughter radionuclide diffuses away from the molecules, daughter radionuclide 109mAg remains on the surface of gold nanoparticles after the decay of 109Pd. To obtain a radiobioconjugate with an affinity for HER2 receptors, polyethylene glycol chains and the monoclonal antibody trastuzumab were attached to the Au@Pd nanoparticles. The synthesized bioconjugate contained an average of 9.5 trastuzumab molecules per one nanoparticle. In vitro cell studies indicated specific binding of the Au@109Pd-PEG-trastuzumab radiobioconjugate to the HER2 receptor on SKOV-3 cells, resulting in 90% internalization. Confocal images illustrated the accumulation of Au@109Pd-PEG-trastuzumab in the perinuclear area surrounding the cell nucleus. Despite the lack of nuclear localization, which is necessary to achieve an effective cytotoxic effect of Auger electrons, a substantial cytotoxic effect, significantly greater than that of pure β− and pure Auger electron emitters was observed. We hypothesize that in the studied system, the cytotoxic effect of the Auger electrons could have also occurred through the damage to the cell's nuclear membrane by Auger electrons emitted from nanoparticles accumulated in the perinuclear area. Conclusion The obtained results show that trastuzumab-functionalized 109Pd-labeled nanoparticles can be suitable for the application in combined β− -Auger electron targeted radionuclide therapy. Due to both components decay (β− and conversion/Auger electrons), the 109Pd/109mAg in vivo generator presents unique potential in this field. Despite the lack of nuclear localization, which is highly required for efficient Auger electron therapy, an adequate cytotoxic effect was attained.